Recommending Collaborators Based on Co–Changed Files: A Controlled Experiment - Constantino, Kattiana; Prates, Raquel; Figueiredo, Eduardo (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2023: Anais do XVIII Simpósio Brasileiro de Sistemas ColaborativosDO - 10.5753/sbsc.2023.229104, 2023)
Active collaboration is essential for the success of software projects across the development life-cycle. However, social coding platforms, like GitHub, present challenges in finding potential collaborators with whom they could create new/stronger ties and enhance the quality of contributions. Thus, we conducted a controlled experiment with 35 participants. We asked participants to perform the experiment tasks to find collaborators with similar interests using a prototype recommendation tool and GitHub. We observed that results confirm that recommender based on co–changed files can provide suitable collaborator recommendations to developers of a specific project.